Infections, Chronic Disease, and the Epidemiological Transition : A New Perspective - Mercer, Alex (Book collections on Project MUSE., 2014)
Examines the ongoing, worldwide epidemiological transition from acute infectious diseases to chronic diseases as the predominant causes of death, presenting a new theory on how chronic diseases have developed.